The endonuclease isoschizomers, SmaI and XmaI, bend DNA in opposite orientations. - Withers, B E (1993)
The SmaI and XmaI endonucleases are imperfect isoschizomers that recognize the sequence CCCGGG. SmaI cleaves between the internal CpG to produce blunt end scissions whereas XmaI cleaves between the external cytosines to produce a four base, five prime overhang. Each of the endonucleases forms stable, specific complexes with DNA in the absence of magnesium. Circular permutation analyses of the protein-DNA complexes revealed that each of the endonucleases induces bending of the DNA. Phase sensitive detection analyses verified the existence of the SmaI and XmaI induced bends. Furthermore, bending of the helix axis by the endonucleases appeared to be directed in opposite orientations. The orientation of the SmaI induced bend appeared to be towards the major groove and is reminiscent of the direction of the bend induced by EcoRV which similarly induces blunt end scissions. Conversely, XmaI appeared to bend the DNA towards the minor groove.